If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2A + 9B + -1C + 3D + 5E + 7F = 138 Solving 2A + 9B + -1C + 3D + 5E + 7F = 138 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-9B' to each side of the equation. 2A + 9B + -1C + 3D + 5E + -9B + 7F = 138 + -9B Reorder the terms: 2A + 9B + -9B + -1C + 3D + 5E + 7F = 138 + -9B Combine like terms: 9B + -9B = 0 2A + 0 + -1C + 3D + 5E + 7F = 138 + -9B 2A + -1C + 3D + 5E + 7F = 138 + -9B Add 'C' to each side of the equation. 2A + -1C + 3D + 5E + C + 7F = 138 + -9B + C Reorder the terms: 2A + -1C + C + 3D + 5E + 7F = 138 + -9B + C Combine like terms: -1C + C = 0 2A + 0 + 3D + 5E + 7F = 138 + -9B + C 2A + 3D + 5E + 7F = 138 + -9B + C Add '-3D' to each side of the equation. 2A + 3D + 5E + -3D + 7F = 138 + -9B + C + -3D Reorder the terms: 2A + 3D + -3D + 5E + 7F = 138 + -9B + C + -3D Combine like terms: 3D + -3D = 0 2A + 0 + 5E + 7F = 138 + -9B + C + -3D 2A + 5E + 7F = 138 + -9B + C + -3D Add '-5E' to each side of the equation. 2A + 5E + -5E + 7F = 138 + -9B + C + -3D + -5E Combine like terms: 5E + -5E = 0 2A + 0 + 7F = 138 + -9B + C + -3D + -5E 2A + 7F = 138 + -9B + C + -3D + -5E Add '-7F' to each side of the equation. 2A + 7F + -7F = 138 + -9B + C + -3D + -5E + -7F Combine like terms: 7F + -7F = 0 2A + 0 = 138 + -9B + C + -3D + -5E + -7F 2A = 138 + -9B + C + -3D + -5E + -7F Divide each side by '2'. A = 69 + -4.5B + 0.5C + -1.5D + -2.5E + -3.5F Simplifying A = 69 + -4.5B + 0.5C + -1.5D + -2.5E + -3.5F
| -4(u-1)=-8u+20 | | A-2B+4C+6D+2E+4F=52 | | -3x+46=-2z+36 | | 2v/5-3wv=40w=10 | | A-B+C-D+E-F=-6 | | 2q+58=4q+50 | | 2s-35=131 | | 1.3h+3.7h=5 | | 50-7k=24 | | 0.8c+9=8(0.6c-2) | | 6(k+4)=3k-12 | | -2x=3x+3 | | 5z-96z+2z+4=12z-156 | | 4x+1=.15 | | 12b+3whenb=-4 | | 1/3=954/s | | 6c=3(c+4)-c | | 5z-96z+2z+4=2(6z-78) | | 1.8=0.03x-58.32 | | 4x+35x=21x+28 | | 2+4(x-7)=5-4(x-5) | | 8x+47=8(x+6) | | -1+3x=3+25x | | 5(3m-4)-8=-88 | | f(x)=x^3-28x+48 | | 6(2x+5)=2 | | x^2+3y^2-3z^2-3xy-2xz-2yz=-1997 | | -3(2g+1)+3g=6g+3 | | 6z-38=130 | | 5n^2+2n-14=-7 | | 9x-58=7x | | (8x-16)=180 |